Survival and Resistance: A Zine Study with Young Women and Femmes Experiencing Housing Injustice in Canadian Cities - Santos Dunn, Nicole; Ansloos, Jeffrey (Engaged Scholar Journal, 2024)
Housing injustice is a serious public health issue among young women and femmes (aged 18-24) in Canada but the research available on this topic seldom centres the voices of people with lived and living experience. This population is marginally visible in the shelter systems; instead their experiences may be described as “hidden homelessness”. This housing typology refers to situations where someone seeks shelter in ways like couch-surfing, car sleeping, or other short-term accommodations that are not typically recognized as responding to housing injustice. Drawing from a methodology of social constructionism, this paper reviews findings from an arts-based inquiry that sought to answer the research question, “what are the survival and resistance strategies that young women and femmes experiencing housing injustice use to support their wellness and engage with life?” Using reflexive thematic analysis, a zine was created and analyzed to reveal five themes: 1). Affective and Psychological Strategies of Resistance; 2). Survival Strategies and Behaviours to Ensure Material Survival; 3). Felt Knowledge About Good Living; 4). Organized Abandonment and Other Normed Chaos; and, 5). Importance of Human Connection, Solidarity, and Radical Care. The strengths and limitations, along with implications for public health policy and research are discussed.